Investigation of subglacial weathering under the Greenland Ice Sheet using silicon isotopes. (15th February 2019) - Hatton, J.E.; Hendry, K.R.; Hawkings, J.R.; Wadham, J.L.; Kohler, T.J.; Stibal, M.; Beaton, A.D.; Bagshaw, E.A.; Telling, J.
Abstract: Subglacial chemical weathering plays a key role in global silicate weathering budgets, contributing to the cycling of silicon (Si) in terrestrial and marine systems and the potential drawdown of carbon dioxide from the atmosphere. Here, we use data from two Greenland Ice Sheet (GrIS) catchments to demonstrate how Si isotopes from dissolved and amorphous particulate fractions (δ 30 DSi and δ 30 ASi respectively) can be used together with major ion data to assess the degree of secondary silicate weathering product formation and redissolution in subglacial environments. We compare a time-series of summer melt seasons from the two study sites, which differ in catchment size (∼600 km 2 for Leverett Glacier (LG) and ∼36 km 2 for Kiattuut Sermiat (KS)). Subglacial waters from LG have elevated Na + and K + ions in relation to Ca 2+ and Mg 2+ ions, indicating a predominance of silicate weathering, whilst meltwaters from KS are characterised by carbonate weathering (hydrolysis and carbonation) throughout the melt season. Both catchments have mean δ 30 DSi values substantially lower than average riverine values (KS 0.41‰, LG −0.25‰, versus a global riverine mean of 1.25‰) and display a seasonal decline, which is more pronounced at LG. The δ 30 ASi values (discharge weighted mean values KS −0.44‰, LG −0.22‰) are lighter than the bedrock (mean values KS −0.18 ± 0.12‰, LG 0.00 ± 0.07‰) in both catchments, indicating a secondary weathering product origin or leaching of lighter isotopes during initial weathering of crushed rock. When used in combination, the major ion and silicon isotope data reveal that the extent of silicate weathering and secondary phase redissolution are more pronounced at LG compared to KS. Contrasting weathering regimes and subglacial hydrology between catchments need to be considered when estimating the δ 30 Si composition of silica exported into polar oceans from the GrIS, with larger catchments likely to produce fluxes of lighter δ 30 Si. As larger catchments dominate freshwater export to the ocean, GrIS meltwater is likely to be very light in isotopic composition, and the flux is likely to increase with ice melt as the climate warms.